Thymoquinone decreases F-actin polymerization and the proliferation of human multiple myeloma cells by suppressing STAT3 phosphorylation and Bcl2/Bcl-XL expression - Badr Gamal; Mohany Mohamed; Abu-Tarboush Faisal (Lipids in Health and Disease, 2011)
Abstract Background Thymoquinone (TQ), the major active component of the medicinal herb Nigella sativa Linn., has been described as a chemopreventive and chemotherapeutic compound. Methods In this study, we investigated the effect of TQ on survival, actin cytoskeletal reorganization, proliferation and signal transduction in multiple myeloma (MM) cells. Results We found that TQ induces growth arrest in both MDN and XG2 cells in a dose- and time-dependent manner. TQ also inhibited CXC ligand-12 (CXCL-12)-mediated actin polymerization and cellular proliferation, as shown by flow cytometry. The signal transducer and activator of transcription (STAT) and B-cell lymphoma-2 (Bcl-2) signaling pathways may play important roles in the malignant transformation of a number of human malignancies. The constitutive activation of the STAT3 and Bcl-2 pathways is frequently observed in several cancer cell lines, including MM cells. Using flow cytometry, we found that TQ markedly decreased STAT3 phosphorylation and Bcl-2 and Bcl-XL expression without modulating STAT5 phosphorylation in MM cells. Using western blotting, we confirmed the inhibitory effect of TQ on STAT3 phosphorylation and Bcl-2 and Bcl-XL expression. Conclusions Taken together, our data suggests that TQ could potentially be applied toward the treatment of MM and other malignancies.